Les enjeux de la grande vitesse ferroviaire dans l’émergence de coopérations interubaines - Guillaume Carrouet (EchoGéo)
The Rhin-Rhône space that includes a collection of agglomerations from Dijon to Bâle, illustrates the stakes of the development of a space enclosed in the Mediterranean Sea-Northern Sea corridor. The arrival of high speed train lines was perceived by the local stakeholders as a favorable contributor to the birth of cooperations through the constitution of a network of cities: the Rhin-Rhône Metropolis. Under the impulsion of the state, this initiative represents a stake for a space whose circulatory dimension is certain. However, after eight years of high speed train service, the results are disappointing considering the initial ambitions. The accessibility stakes may have federated the local stakeholders, but the desired territorial development close to each train station has weakened this cooperation perspectice. Reflective of that: the redundancy of zones of activity in tertiary focus resulted in medium agglomerationes, only separated by around 100 kilometers.